The Role of Triglyceride-rich Lipoproteins and Their Remnants in Atherosclerotic Cardiovascular Disease - Mohanad Gabani; Michael D Shapiro; Peter P Toth (European Cardiology Review)
Atherosclerotic cardiovascular disease (ASCVD) is the world’s leading cause of death. ASCVD has multiple mediators that therapeutic interventions target, such as dyslipidaemia, hypertension, diabetes and heightened systemic inflammatory tone, among others. LDL cholesterol is one of the most well-studied and established mediators targeted for primary and secondary prevention of ASCVD. However, despite the strength of evidence supporting LDL cholesterol reduction by multiple management strategies, ASCVD events can still recur, even in patients whose LDL cholesterol has been very aggressively reduced. Hypertriglyceridaemia and elevated levels of triglyceride-rich lipoproteins (TRLs) may be key contributors to ASCVD residual risk. Several observational and genetic epidemiological studies have highlighted the causal role of triglycerides within the TRLs and/or their remnant cholesterol in the development and progression of ASCVD. TRLs consist of intestinally derived chylomicrons and hepatically synthesised very LDL. Lifestyle modification has been considered the first line intervention for managing hypertriglyceridaemia. Multiple novel targeted therapies are in development, and have shown efficacy in the preclinical and clinical phases of study in managing hypertriglyceridaemia and elevated TRLs. This comprehensive review provides an overview of the biology, pathogenicity, epidemiology, and genetics of triglycerides and TRLs, and how they impact the risk for ASCVD. In addition, we provide a summary of currently available and novel emerging triglyceride-lowering therapies in development.